1978
DOI: 10.1063/1.90448
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of indium tin oxide (ITO)/polycrystalline silicon solar cells

Abstract: Efficient indium tin oxide (ITO)/polycrystalline silicon heterojunction solar cells have been fabricated utilizing neutralized ion-beam sputtering techniques. These cells were fabricated on single-pass float-zone-refined silicon. Conversion efficiencies of 6.25% under AM1 illumination have been observed. Cells were analyzed by I-V characteristics and a scanning laser photoresponse technique. Qualitative minority-carrier lifetime has been mapped using the EBIC mode of a SEM. This has revealed a reduced photores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It also revealed that, reduction of output of polycrystalline cells is not directly depends on grain boundaries as their area of impact is low compared to total area. In contrary, a notable reduction in photocurrent and barrier height can be caused by the background defects (Cheek et al, 1978).…”
Section: Research Work On Schottky Solar Cell In Chronological Ordermentioning
confidence: 97%
See 1 more Smart Citation
“…It also revealed that, reduction of output of polycrystalline cells is not directly depends on grain boundaries as their area of impact is low compared to total area. In contrary, a notable reduction in photocurrent and barrier height can be caused by the background defects (Cheek et al, 1978).…”
Section: Research Work On Schottky Solar Cell In Chronological Ordermentioning
confidence: 97%
“…The following table gives some clear idea about the materials of the top layer. Though these are the possible materials those can be used in MIS/SIS cells but mainly ZnO [18] , AZO (Fuchsel;Jia et al, 2013;Bethge), ITO (Cheek et al, 1978;Ashok et al, 1980;Saha et al, 1983;Saim et al, 1987;Simashkevich et al, 2004;Malik et al, 2008;Bruk et al, 2009;Liu et al, 2010;Du et al, 2015;Du et al, 2017) are used by most of the researchers. Another material which is very popular for n-type base material is Graphene (Li et al, 2010;Feng et al, 2012;Miao et al, 2012;Liu et al, 2015;Song et al, 2015).…”
Section: Suitable Materials For Top Layermentioning
confidence: 99%
“…Similar problems exist in the fabrication of oxide semiconductors. In the case of ITO, several methods for deposition; i.e., ion-beam sputtering [28], de and rf sputtering [29], electron-beam deposition [30], and spray technology [6] have all been utilized in the fabrication of solar cells. Efficient solar cells have been fabricated by several methods on both n-and p-type silicon.…”
Section: Caleulation Of the Effieie!iii!!fmentioning
confidence: 99%
“…Imperfections in silicon can cause efficiency variations across solar panels . For this reason, researchers developed LBIC to characterize the reproducibility and quality of solar panels on the assembly line . In a typical LBIC imaging experiment, a focused laser spot illuminates a small spot on the solar cell while an ammeter or potentiometer measures current or voltage from the cell .…”
Section: Introductionmentioning
confidence: 99%